Potassium doses in previous crops and effect on soybean in succession - João W. Bossolani; Edson Lazarini; Luiz G. M. de Souza; Tiago de L. Parente; Sheila Caioni; Naira Q. de Biazi (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Early potassium fertilization in previous crops may be beneficial to the main crop in succession. The objective of this study was to investigate the behavior of the soybean crop as a function of potassium (K) doses in the previous crops, associated or not with K application in soybean. The experiment was carried out from 2012 to 2015 in an experimental area of the Faculty of Engineering, UNESP, Campus of Ilha Solteira-SP, located in Selvíria-MS, Brazil. For the previous crops, a randomized block design was used in a 3 x 4 factorial scheme with four replications, i.e., three previous crops (maize, sorghum and millet) and four K doses (0, 35, 70 and 120 kg ha-1 of K2O). For soybean in succession, a randomized complete block design was used in the split-plot scheme. The treatments were arranged in a 3 x 4 x 2 factorial scheme with four replicates, i.e., soybean sowing on three types of straw (maize, sorghum and millet), residual of the four K doses and with or without top-dressing K fertilization in the soybean. Millet accumulated higher K content in comparison to maize and sorghum. The return of K to the system by millet is similar to that by maize. Potassium doses in the previous crops do not alter their dry matter production and K content. Potassium fertilization in the soybean crop in succession to millet allows higher yields.